Learning to live with nature - Kunešová, Květuše (Ondina - Ondine, 2022)
The article is an analysis of the novel The Sun rises in the North by Doric Germain, a Franco-Ontarian writer. The theme is definitely "Canadian" considering it is a return to nature. The protagonist of the story is Marc Bérard, a seventeen-year-old teenager. His mother dead, his father hospitalized, he must close the door on what is familiar to him, that is to say the city: the cobbled streets, the skyscrapers and the material comforts of city life. Overnight, he finds himself at his uncle’s home in the great spruce forest of the North, where life is a constant struggle against the wilderness. But this nature reserves its treasures and secrets for those who know how to tame it. A few months will suffice to make Marc a young man confident in the future and in his abilities. Although the starting point of our approach is sociological, the methodology adopted allows a more complex analysis of the novel. The sociological perspective is balanced by that focused on questions of identity because this is a Bildungsroman. The role of the environment in human life is indisputable, nature considered more and more a counterweight to urban civilization. Doric Germain’s novel represents an original approach to the theme of the relationship between nature and man. The value of the story lies in this specific image of non-urban inhabited space. Keywords: urban civilisation, rural world, nature, Bildungsroman, Quebec literature